Allosteric Indicator Displacement Enzyme Assay for a Cyanogenic Glycoside. Issue 43 (7th October 2013) - Jose, D. Amilan; Elstner, Martin; Schiller, Alexander
Abstract Indicator displacement assays (IDAs) represent an elegant approach in supramolecular analytical chemistry. Herein, we report a chemical biosensor for the selective detection of the cyanogenic glycoside amygdalin in aqueous solution. The hybrid sensor consists of the enzyme β‐glucosidase and a boronic acid appended viologen together with a fluorescent reporter dye. β‐Glucosidase degrades the cyanogenic glycoside amygdalin into hydrogen cyanide, glucose, and benzaldehyde. Only the released cyanide binds at the allosteric site of the receptor (boronic acid) thereby inducing changes in the affinity of a formerly bound fluorescent indicator dye at the other side of the receptor. Thus, the sensing probe performs as allosteric indicator displacement assay (AIDA) for cyanide in water. Interference studies with inorganic anions and glucose revealed that cyanide is solely responsible for the change in the fluorescent signal. DFT calculations on a model compound revealed a 1:1 binding ratio of the boronic acid and cyanide ion. The fluorescent enzyme assay for β‐glucosidase uses amygdalin as natural substrate and allows measuring Michaelis–Menten kinetics in microtiter plates. The allosteric indicator displacement assay (AIDA) probe can also be used to detect cyanide traces in commercial amygdalin samples.